2009
DOI: 10.3174/ajnr.a1450
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia of L5 and Wedging and Pseudospondylolisthesis in Patients with Spondylolysis: Study with MR Imaging

Abstract: BACKGROUND AND PURPOSE:The association between L5 hypoplasia and bilateral spondylolysis was described earlier on conventional radiographs of the lumbar spine. The purpose of this study was to describe the findings on MR imaging in patients with hypoplasia of L5 and to correlate these findings with the presence of bilateral spondylolysis of L5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…We showed that the incidence of such a difference in length is particularly frequent in the distal part of the lumbar spine. Hypoplastic vertebral bodies were previously diagnosed by visual assessment of the alignment on conventional X-rays [ 21 ] or by measuring the vertebral bodies on mid-vertebral level on MRI [ 26 ]. In the presence of scalloping vertebral bodies, this method can underestimate the true level of bony support for the intervertebral disc ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that the incidence of such a difference in length is particularly frequent in the distal part of the lumbar spine. Hypoplastic vertebral bodies were previously diagnosed by visual assessment of the alignment on conventional X-rays [ 21 ] or by measuring the vertebral bodies on mid-vertebral level on MRI [ 26 ]. In the presence of scalloping vertebral bodies, this method can underestimate the true level of bony support for the intervertebral disc ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For each patient, we measured three motion segments for a total of 201 motion segments. Frank and Miller [ 21 ] and Wilms et al [ 26 ] assessed the middle of the vertebra. However, scalloping vertebral bodies, shown in Figure 2 , confounded the results; therefore, a modified measuring approach was used to compare the two adjacent endplates as shown in Figure 3 ; only the effective, weight-bearing, bony area was measured and is shown in Figure 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Wilms G. et al (11) submitted that 'L5 hypoplasia is a frequent finding in patients with bilateral spondylolysis.' Niggemann et al (4) submitted that vertebral hypoplasia is a common diagnosis as 42% of their cases with isthmic spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although in both studies the detection rates of hypoplasic vertebra were very close to each other, it is seen that in these studies different methods were used to measure hypoplasia. Wilms et al (11) calculated anteroposterior diameter L5 vertebrae was measured at the mid-vertebral zone on the midsagittal MR images. For the measurement of S1 vertebrae, they used upper vertebral surface on the same MR plan.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic predisposition also favours this site irrespective of being degenerative or isthmic. Progression of wedge values down the spine, increase in caudal vertebral body height with decrease in posterior elements in the lower lumbar region to create lumbar lordosis encourage spondylolisthesis [22]. Furthermore, the increased incidence of L5 spondylolisthesis could be due to the complementary role of anterior-posterior lumbo-sacral radiograph.…”
Section: Discussionmentioning
confidence: 99%